Hubungan Tingkat Pengetahuan dengan Self-Efficacy Lansia dalam Manajemen Osteoartritis Knee pada Lansia - Dwi Purwantini; Sisilia Indriasari Widianingtyas; Yunita Wiguna (Jurnal Keperawatan Florence Nightingale, 2026)
Knee osteoarthritis is one of the most common degenerative joint diseases in the elderly and is a major cause of pain, reduced mobility, and poor quality of life. Education and structured exercise can reduce pain, improve quality of life, and increase self-efficacy. This study aims to determine the relationship between knowledge and self-efficacy in managing knee osteoarthritis among the elderly. The study design was correlational and cross-sectional, using an osteoarthritis knowledge questionnaire to assess knowledge level and the Arthritis Self-Efficacy Scale-8 (ASES-8) to assess self-efficacy as data collection tools. The research sample consisted of 34 elderly people diagnosed with knee OA based on ACR clinical criteria at the Elderly Health Center in RW 6, Wadungasri Village, Waru District, Sidoarjo. The sampling technique used was purposive sampling. The results showed that the majority of subjects were female (94.1%), aged 60-79 years (97%), and overweight to obese (82.3%). The level of knowledge among the elderly was mostly in the adequate (61.8%) and good (29.4%) categories. The level of self-efficacy was in the moderate to high and high categories (82.4%). The correlation test results show that there is no significant relationship between education and self-efficacy (ρ= 0.034; p= 0.849). These findings indicate that self-efficacy is not only influenced by cognitive knowledge, but is more influenced by direct practical experience through participatory education. These findings suggest that self-efficacy among older adults with knee osteoarthritis may be influenced by factors beyond knowledge alone, including practical experience and social support.